PENGEMBANGAN USAHA KULINER â€œWAROENG MAKAN TEPI LAUTâ€ DI KAWASAN MEGA MAS, KOTA MANADO - Angraini ., Datunsolang; Jenny Baroleh; Benu Olfie L.S. (Sam Ratulangi University, 2016)
This study aims to describe how the development of a culinary efforts and make an assessment as the basis to determine the culinary business development. This study began in March until June 2016. This research located in